Detecting and Correcting for Paleomagnetic Inclination Shallowing of Sedimentary Rocks: A Review - Li, Yong-Xiang; Kodama, Kenneth P. (Frontiers in Earth Science, 2016)
Magnetic anisotropy and the elongation/inclination (E–I) approaches have been increasingly employed as two important means for detecting and correcting the paleomagnetic inclination shallowing in sedimentary rocks that was first recognized 60 years ago. Both approaches are based on certain assumptions, and thus have advantages and intrinsic limitations in investigating shallow inclinations in sedimentary rocks. The E–I approach is relatively easy to use, but it needs a large dataset to adequately sample paleomagnetic directions due to paleosecular variation (PSV) of the geomagnetic field. Also, slow sediment accumulation rates (SARs) and local tectonics could lead to under- or over-corrections using the E–I approach. For the magnetic anisotropy technique, labor-intensive, sophisticated laboratory rock magnetic experiments are required in order to accurately determine both bulk magnetic anisotropy of remanence-carrying grains and magnetic anisotropy of an individual particle, i.e., “a” factor, of samples. Our review shows that, despite the intensive laboratory work necessary for applying anisotropy-based inclination corrections, it is worth investing the effort. In addition, the joint use of magnetic susceptibility and remanence anisotropy measurements as well as detailed rock magnetic measurements for determining the particle anisotropy “a” factor have the advantage of retrieving direct evidence of inclination shallowing and correcting for it with high confidence. We caution against use of either of the two approaches without full appreciation of the underlying assumptions and intrinsic limitations of each technique. The use and comparison of both techniques could provide the most robust inclination shallowing correction for sedimentary rocks.